SEVENTH GRADERS’ VOCABULARY LACKNESS IN WRITING SKILL THROUGH KURIKULUM MERDEKA IMPLEMENTATION AT SMP SWASTA BNKP IDANOGAWO - Rutdesrin Waruwu; Yasminar Amaerita Telaumbanua; Afore Tahir Harefa; Riswan Zega (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Vocabulary mastery is very important for writing, but many junior high school students still experience difficulties due to limited vocabulary. This study aims to describe the influence and factors that cause students to lack vocabulary. Using a descriptive qualitative approach, data were collected through checklist observations and structured interviews with one English teacher and 20 students. Findings indicate that limited vocabulary significantly influence students’ ability to construct complete sentences, as they often use inappropriate words or make mistakes in word choice (diction) and struggle to express their ideas clearly and structurally. The factors contributing to students’ limited vocabulary include internal and external aspects. Internally, these include low motivation and interest in learning English and weak foundational education. Externally, these include limited access to learning facilities and resources. This study concludes that improving vocabulary proficiency is very important for improving writing quality and recommends that future researchers conduct quantitative research to test the extent to which improved vocabulary proficiency directly influences the quality of students’ writing in terms of content, sentence structure, and completeness of information